2020
DOI: 10.1016/j.joep.2019.102210
|View full text |Cite
|
Sign up to set email alerts
|

Motivational crowding out effects in charitable giving: Experimental evidence

Abstract: This paper tests motivational crowding out in the domain of charitable giving. A novelty is that our experiment isolates alternative explanations for the decline of giving such as strategic considerations of decision makers. Moreover, preference elicitation allows us to focus on the reaction of donors characterized by different degrees of intrinsic motivation. In the charitable-giving setting subjects donate money to the German "Red Cross" in two consecutive stages. The first dictator game is modified, i.e., d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The results were largely consistent with those using the whole sample. 9 Third, research shows women tend to demonstrate more philanthropic behavior than men (Bekkers, 2003; Women’s Philanthropy Institute, 2015) and are more risk averse than men (Müller & Rau, 2016), so our imbalanced panel is grounded in some aspect of reality.…”
Section: Discussionmentioning
confidence: 99%
“…The results were largely consistent with those using the whole sample. 9 Third, research shows women tend to demonstrate more philanthropic behavior than men (Bekkers, 2003; Women’s Philanthropy Institute, 2015) and are more risk averse than men (Müller & Rau, 2016), so our imbalanced panel is grounded in some aspect of reality.…”
Section: Discussionmentioning
confidence: 99%
“…Communicating the increased marginal impact of blood donation causes greater donation willingness of non-donors at the extensive margin, and affects the temporal donation willingness of both donors and non-donors. Further, shortage information does not cause crowding-out (Müller & Rau, 2020). On the other hand, the reduced willingness to donate when given hygiene information is important for policymakers and practitioners to consider and in contrast to the results of Ou-Yang et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of normative studies explored the crowding-out effect extrinsic incentives impose on intrinsic motivation (Deci et al, 1999; Müller & Rau, 2020) and prosocial motivation in particular (Frey, 1997; Frey & Götte, 1999). For instance, Chao (2017) conducted a field experiment and found that offering thank-you gifts as an incentive, in fact, reduced donation rates (i.e., the number of people reminded to donate divided by the number of donors) in a fundraising campaign.…”
Section: The Discrepancy Between Laypeople’s Belief and Normative Stu...mentioning
confidence: 99%